Khūm̄ư kānčhat kitčhakam rīanrū prachāthipatai samrap khrū phūs̨ōn chan prathomsưksā pī thī 1-3. (Samnakngān Khana Kammakān Kānl̄ưaktang : Samnakngān Khana Kammakān Kānsưksā Khan Ph̄ưnthān, Krasūang Sưksāthikān, 2009)
Educational activities for the understanding of democracy for Thai elementary school children from grades one to three.